Tres notas de lectura a los epilios profanos de Draconcio - Paniagua, David (Exemplaria Classica, 2009)
This paper diverges from traditional exegesis to propose different interpretations on three passages of Dracontius’ Carmina profana (Romul. 8, 3-6, Romul. 10, 477-482 and Romul. 10, 293-295).